Rumen degradation and nutritive utilization of wheat straw, corn stalks and sugarcane bagasse ensiled with multienzymes. Issue 1 (1st January 2017) - Gado, H. M.; Elghandour, M. M. Y.; Cipriano, M.; Odongo, N. E.; Salem, A. Z. M.
ABSTRACT: The aim of this study was to determine the effect of anaerobic ensiling of raw agricultural wastes with a fibrolytic enzyme cocktail (EZ) as a cleaner and sustainable biological product for animal feed. Ten 1-kg samples of wheat straw, corn stalks and sugarcane bagasse were chopped at 5 cm length and mixed with EZ at three levels of 0, 1 or 3 L enzyme/ton of feed, moistened to a relative humidity of approximately 50% and ensiled in plastic bales for 30 days. Additionally, fibrous samples were incubated for 72 h with rumen liquor to determine the digestion of dry matter (DM), neutral detergent fibre and acid detergent fibre. Increasing enzyme level lowered ether extract and nitrogen-free extract contents of fibrous feeds and increased the biodegradation of acid detergent lignin of wheat straw. Anaerobic ensiled corn stalks and sugarcane bagasse with EZ improved the biodegradation of DM and fibre fractions. It could be concluded that ensiling fibres of the three wastes with EZ improved and enhanced their ruminal digestion with the biodegradation rate at 3 L/ton and subsequently produced a cleaner product for animal feed from agriculture wastes.